The Study on sowing time effect on millet (Panicum miliaceum.L) green mass in the central (Mongolian Journal of Agricultural Sciences, 2021)
The one of the best crops grown in Mongolia is Mongolian rice, which is drought-tolerant, has a good reproductive ability, easy processing and easy to prepare for food. The study was conducted in the field of the Institute of Plant and Agriculture Science in Khongor soum of Darkhan-Uul aimag in 2017-2019. The variety named Saratovskaya 853 was  sown in the 10 June, 20 June and 10 June. Millet variety Saratovskaya 853 was planted in the 9 research stages /a stage covers 3m2/ and, they were spacing between 0.5 m from each other. The millet seed were planted in the 6 centimeter deep from ground and planted in the lines between 15 centimeters. During this study, we planted 3 million seed per hectare in 3 times repetition. When millet was grown for green fodder, the field germination rate was 76.4-77.2 percent. The crop version of the 10.June was 308.8 c/ha green mass, which is higher 42.6-82.6 c/ha, but the grass yield was 83.6 c / ha, which is higher respectively 31.0-29.2 c / ha than other crop version.Тариалангийн төв бүсэд бог будаа (Panicum miliaceum.L)-ны ногоон массын  ургацад тарих  хугацааны нөлөөБог будаа нь хүнс, тэжээлийн нэг наст  үет  ургамал. Манай орны тариачин ардууд ганд тэсвэртэй,үржих чадвар өндөр, боловсруулах багаж төхөөрөмжийн шаардлага бага, хүнс тэжээлд хэрэглэхэд амар хялбар зэрэг өвөрмөц онцлогтой түгээмэл тариалагдаж байсан унаган таримлын нэг бол бог будаа юм[4]. Туршлага судалгааг 2017-2020 онд Дархан-Уул аймгийн Хонгор сумын нутаг дахь УГТХүрээлэнгийн судалгааны талбарт  явууллаа. Бог будааны Саратовская-853 сортыг  мөр хооронд 15 см зайтайгаар 6 см гүнд 6 дугаар сарын 10,20, 30 гэсэн хугацаанд  нэг га талбайд 3 сая.ширхэг нормоор тус бүр 3 давталтайгаар нэг дэвсгийн хэмжээ 3м2  нийт 9 дэвсэгт тариалсан. Бог будааг ногоон тэжээлд зориулан тариалахад судалгаа  явуулсан  жилүүдийн хээрийн цухуйц 76.4-77.2 хувийн цухуйцтай байлаа. Ногоон массын ургацаар  6 дугаар сарын 10-ны хугацааны хувилбар 308.8 ц/га ногоон массын ургацыг бүрдүүлж  бусад хугацааны хувилбараас 42.6-82.6 ц/га, өвсний 83.6  ц/га ургацыг бүрдүүлж  бусад хугацааны хувилбараас 31.0-29.2 ц/га  ургацаар  тус тус илүү байлаа. Түлхүүр үг:  Талбай, хувилбар, давталт, өвс, чанар